Mpox: A case study for a one health approach to infectious disease prevention - David T.S. Hayman; Marion P.G. Koopmans; Andrew A. Cunningham; Salome A. Bukachi; Leandre Murhula Masirika; Wanda Markotter; Thomas C. Mettenleiter (One Health)
Mpox has been declared a global health emergency twice by the World Health Organization due to its impacts within and beyond Africa. Enzootic in Central and West African wildlife, mpox outbreaks have resulted from zoonotic spillover, with recent events revealing increased human-to-human transmission. Factors like population growth and environmental disruption, alongside reduced smallpox immunity, increase emergence risk. In addition, the emergence in South Kivu of a distinct subclade of mpox virus points at a currently understudied aspect of mpox virus lineages and their dynamics in reservoir hosts. A One Health approach—integrating human, animal, and environmental science—is essential for reducing the risk of mpox emergence. This approach should encompass ecological studies to understand putative reservoir population dynamics and the potential for interventions, reducing activities that increase human-animal contacts, respectful community engagement to reduce spillover risk from cultural practices (such as hunting multiple species of wildlife for consumption), and socially acceptable and equitable access to medical and non-medical countermeasures to prevent or control ongoing human-to-human transmission. Politically supported collaborative efforts across disciplines with involvement of stakeholders are critical to promote and strengthen socially and environmentally sustainable practices to mitigate future outbreaks.